Gesture recognition with application to human-robot interaction - Mangera, Ra'eesah (Department of Electrical Engineering, 2015)
Gestures are a natural form of communication, often transcending language barriers. Recently, much research has been focused on achieving natural human-machine interaction using gestures. This dissertation presents the design of a gestural interface that can be used to control a robot. The system consists of two modes: far-mode and near-mode. In far-mode interaction, upper-body gestures are used to control the motion of a robot. Near-mode interaction uses static hand poses to control a graphical user interface. For upper-body gesture recognition, features are extracted from skeletal data. The extracted features consist of joint angles and relative joint positions and are extracted for each frame of the gesture sequence. A novel key-frame selection algorithm is used to align the gesture sequences temporally. A neural network and hidden Markov model are then used to classify the gestures. The framework was tested on three different datasets, the CMU Military dataset of 3 users, 15 gestures and 10 repetitions per gesture, the VisApp2013 dataset with 28 users, 8 gestures and 1 repetition/gesture and a recorded dataset of 15 users, 10 gestures and 3 repetitions per gesture. The system is shown to achieve a recognition rate of 100% across the three different datasets, using the key-frame selection and a neural network for gesture identification. Static hand-gesture recognition is achieved by first retrieving the 24-DOF hand model. The hand is segmented from the image using both depth and colour information. A novel calibration method is then used to automatically obtain the anthropometric measurements of the user’s hand. The k-curvature algorithm, depth-based and parallel border-based methods are used to detect fingertips in the image. An average detection accuracy of 88% is achieved. A neural network and k-means classifier are then used to classify the static hand gestures. The framework was tested on a dataset of 15 users, 12 gestures and 3 repetitions per gesture. A correct classification rate of 75% is achieved using the neural network. It is shown that the proposed system is robust to changes in skin colour and user hand size.